Altered Tregs Differentiation and Impaired Autophagy Correlate to Atherosclerotic Disease - Mandatori, Sara; Pacella, Ilenia; Marzolla, Vincenzo; Mammi, Caterina; Starace, Donatella; Padula, Fabrizio; Vitiello, Laura; Armani, Andrea; Savoia, Carmine; Taurino, Maurizio; De Zio, Daniela; Giampietri, Claudia; et al. (Frontiers in Immunology, 2020)
Atherosclerosis is a progressive vascular disease representing the primary cause of morbidity and mortality in the developed countries. Formerly, atherosclerosis was considered as a mere passive accumulation of lipids in blood vessels. However, it is now clear that atherosclerosis is a complex and multifactorial disease, in which the involvement of immune cells and inflammation play a key role. A variety of studies have shown that autophagy - a cellular catalytic mechanism able to remove injured cytoplasmic components in response to cellular stress - may be pro-atherogenic. So far, in this context, its role has been investigated in smooth muscle cells, macrophages and endothelial cells, while the function of this catabolic protective process in lymphocytes functionality has been overlooked. The few studies carried out so far, however, suggested that autophagy modulation in lymphocytes subsets may be functionally related to plaque formation and development. Therefore, in this research, we aimed at better clarifying the role of lymphocytes subsets, mainly regulatory T cells (Tregs), in human atherosclerotic plaques and in animal models of atherosclerosis investigating the contribution of autophagy on immune cells homeostasis. Here we investigate basal autophagy in a mouse model of atherosclerosis, ApoE knock-out (KO) mice, and we further analyze the role of autophagy in driving Treg cells polarization. We observed defective maturation of Tregs from ApoE-KO mice in response to TGFβ. TGFβ is a well-known autophagy inducer, and Tregs maturation defects in ApoE-KO mice seem to be related to autophagy impairment. In this work we propose that autophagy underlies Tregs maturation, advocating that the study of this process in atherosclerosis may open new therapeutic strategies.